Acting in the public interest - Mohd. Sulaiman, Aiman @ Nariman; Yong, Johnny (Malaysian Insitute of Accountants, 2024)
Members of the accountancy profession are familiar with the assertion that “a distinguishing mark of the accountancy profession is its acceptance of the responsibility to act in the public interest.” This hallmark is stated in the Code of Ethics (the Code) of the International Ethics Standards Board for Accountants (IESBA), which has been fully incorporated into the MIA By-Laws. Nonetheless, within academia and the accountancy profession, this aspect of the Code which is found in paragraph 100.1 of the MIA By-Laws, has been viewed as a challenge to professional accountants (PAs) in performing their role and necessitates further clarification and guidance. Questions commonly posed include: (a) who is the face of the public interest that the accountant is expected to serve? (b) who could possibly be the “other stakeholders” whose interest the accountant must consider? and (c) how does the PA possibly reconcile and balance the divergent interests of all these stakeholders, assuming that they can be identified?